IMF Staff papers : Volume 6 No. 3. (IMF Staff Papers; IMF Staff Papers, 1958)
This paper explores wage-price link in a prolonged inflation. A fixed tie between wages and prices must have significant effects in any economy. A wage-price link of the type discussed in this paper assumes that wages will be adjusted for any rise in consumer prices, subject to certain safeguards. This will protect wage earners against any significant fall in real wages arising from investment inflation. For a free economy, in which economic adjustments are induced by changes in prices and wages, the imposition of the degree of rigidity implied by this association is of far-reaching importance. in several countries, the use of wage-price links is a consequence of the fear of labor that real wages will be adversely affected by inflation. Although the basic causes of inflation vary widely in different countries and at different times, the process of inflation always shows similar characteristics. In an economy which is functioning properly, the distribution and use of the gross national product should result in an aggregate demand for goods and services that tend to equal the available supply of goods and services at approximately stable prices.